Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Catalyst deactivation and regeneration - Satyanarayana, C. V.; Srikant, D.; Gurav, H. R. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalysis plays a vital role in the manufacture of fuels, industrial chemicals, fine chemicals, and specialty chemicals. A catalyst is not only expected to be highly active, it should be stable for long hours on stream and should be recyclable, if required. However, in reality, all the catalysts have finite life. Hence, a most important goal of any catalyst development is to get a catalyst that is highly active for long periods without needing any regeneration. This chapter addresses various causes of catalyst deactivation with reference to different catalyst systems. It discusses various forms coke (carbon) forms on catalysts and the side reactions that drive their formation. The role of support on carbon formation as well as how carbon can be limited using bimetallic catalysts is discussed. Various mechanisms responsible for sintering of metals have been discussed while suggesting means to suppress the same. This chapter also discusses loss of catalyst activity due to strong chemisorption of impurities or byproducts. Typical poisons to different catalysts are listed. The effect of various poisons and how they can influence the course of a catalytic reaction are described. A catalyst may also lose its activity due to mechanical failures such as (i) crushing of catalyst pellets or granules, (ii) breakup of catalyst pellets followed by its attrition, and (iii) erosion of catalyst particles or monolith wash coats. Various solutions to prevent or delay catalyst deactivation as well as various catalyst regeneration methods are summarized.